Development of spake's maintenance module for Ministry of Defence Malaysia / [compact disc] - 408017 Syed Ardi Syed Yahya Kamal (2004)
Thesis Sarjana (Kejuruteraan Perisian)) - Universiti Teknologi Malaysia, 2004